Asesmen Risiko Gangguan Saluran Kabel Tegangan Menengah 20 kV Menggunakan Metode Bow Tie pada PT X - Syaiful Azhari Siregar; Suparno Suparno (G-Tech: Jurnal Teknologi Terapan, 2024)
As one of the operational units of PT PLN (Persero) operated in the distribution and customer service processes, the reliability of the distribution network is a critical concern for PT X. This study conducts a three-stage assessment of the risks associated with disturbances in the 20 kV medium voltage cable network at PT X. In the first stage, a bow-tie diagram comprising 10 threats, 4 consequences, and 18 risk control activities, is developed. In the second stage, the risk level is determined, beginning with assessing likelihood, impact level, and risk control effectiveness. By mapping these results on the risk matrix, it was concluded that the risk level was in the “High” category. In the final stage, the effectiveness of risk controls is ranked to determine the priority for improving risk control activities. 7 activities are identified as requiring immediate attention due to their current ineffective implementation.